2022
DOI: 10.1186/s40798-022-00422-1
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Physical Exercise Interventions Participation and Functional Capacity in Individuals with Type 2 Diabetes: A Systematic Review and Meta-Analysis of Controlled Trials

Abstract: Background The prevalence of type 2 diabetes mellitus increases with age, and people with type 2 diabetes are more affected by reductions in functional performance. Although exercise interventions are recommended for people with diabetes, it is relevant to assess the effects of different training modes on the available functional outcomes. Therefore, our purpose was to systematically assess the effect of different physical exercise modalities in patients with type 2 diabetes with an average age… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
(124 reference statements)
0
6
0
Order By: Relevance
“… 80 Recently, a meta-analysis indicated that structured physical exercise programmes, including aerobic training, combined training and resistance training, might improve functional capacity assessed by the 6-minute walk test (51.6 m, 95% CI 7.6%, 95.6%; I 2 92%), one-repetition maximum leg-press (18.0 kg, 95% CI 4.0%, 31.9%; I 2 0%), and maximum oxygen consumption (2.41 mL/kg min, 95% CI 1.89%, 2.92%; I 2 100%) in patients with T2DM. 88 Interestingly, a recent study also indicated that a virtual multidisciplinary intensive lifestyle intervention was as effective as in-person intervention programmes aimed at increasing body weight loss, improving metabolic profile and reducing medication in patients with T2DM and obesity. 89 Table 2 90 93 summarizes the health benefits and safety issues associated with various exercise programmes, and Figure 2 summarizes the physiological aspects of exercise metabolism and how they benefit T2DM and obesity prevention.…”
Section: Exercise Interventions For the Management Of Obesity And Typ...mentioning
confidence: 99%
See 1 more Smart Citation
“… 80 Recently, a meta-analysis indicated that structured physical exercise programmes, including aerobic training, combined training and resistance training, might improve functional capacity assessed by the 6-minute walk test (51.6 m, 95% CI 7.6%, 95.6%; I 2 92%), one-repetition maximum leg-press (18.0 kg, 95% CI 4.0%, 31.9%; I 2 0%), and maximum oxygen consumption (2.41 mL/kg min, 95% CI 1.89%, 2.92%; I 2 100%) in patients with T2DM. 88 Interestingly, a recent study also indicated that a virtual multidisciplinary intensive lifestyle intervention was as effective as in-person intervention programmes aimed at increasing body weight loss, improving metabolic profile and reducing medication in patients with T2DM and obesity. 89 Table 2 90 93 summarizes the health benefits and safety issues associated with various exercise programmes, and Figure 2 summarizes the physiological aspects of exercise metabolism and how they benefit T2DM and obesity prevention.…”
Section: Exercise Interventions For the Management Of Obesity And Typ...mentioning
confidence: 99%
“…87 In addition, aerobic exercise significantly induces weight loss, promotes glycaemic control, improves HbA1c levels, and improves lipid and lipoprotein metabolism. 80 88 Interestingly, a recent study also indicated that a virtual multidisciplinary intensive lifestyle intervention was as effective as in-person intervention programmes aimed at increasing body weight loss, improving metabolic profile and reducing medication in patients with T2DM and obesity. 89 Table 2 [90][91][92][93] summarizes the health benefits and safety issues associated with various exercise programmes, and…”
Section: Exercise Interventions For the Management Of Obesity And Typ...mentioning
confidence: 99%
“…Previous reviews have reported the beneficial effect of exercise in increasing functional capacity for hypertension [ 14 ]. type 2 diabetes [ 15 ]. or cardiovascular disease [ 1 , 8 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recommended PA types for people with diabetes include aerobic exercise, strength, endurance, flexibility, and balance training [ 24 ]. PA confers positive effects in terms of physical (immune system, blood lipid profile, blood pressure, cardiovascular disease, endothelial function, and physical fitness) [ 25 , 26 , 27 ] and mental health [ 28 , 29 ]. Consequently, PA could be a positive lifestyle modification with multiple health benefits for the disease [ 6 , 28 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%